MANAJEMEN POWERFULL (ALTERNATIF STRATEGI BELAJAR) - Dahliah Dahliah (Conciencia, 2016)
Directions of coaching and improving the quality of teachers should be oriented towards the establishment of effective teachers, namely teachers who were willing and able to leverage the entire potential of the internal and external optimally (powerful) to achieve education goals maximally effective teachers would be different from usual teachers. Effective teachers would give a touch that was relatively well targeted and more oriented towards building motivation. This was what distinguished effective teachers with usual teachers was simply teaching and giving material according to curriculum without accompanied of the implementation of the functions of the teacher's own personality